Do familiarity and awareness influence voting intention: The case of road pricing reform?. (December 2017) - Balbontin, Camila; Hensher, David A.; Collins, Andrew T.
Abstract: The choices that individuals make are influenced by the attributes defining alternatives from which to choose as well as their socioeconomic characteristics and beliefs. The literature on choice modelling which informs the decision making process implicitly assumes that individuals are both aware of and familiar with the alternatives being assessed. As far as we are aware, there is limited experience of the role that familiarity and awareness play in conditioning the choice behaviour of individuals. This paper investigates the role of awareness and familiarity in a context of growing interest, namely road pricing reform. Specifically, we analyse how the level of familiarity with the road pricing debate and the awareness of what road pricing means might influence the preferences of individuals for cordon-based and distance-based charging regimes, in contrast to the status quo. Familiarity and awareness are introduced into a choice model that allows for risk attitude, source preference and perceptual conditioning from the attribute level's variation over repeated occurrences, as well as the perceived acceptability of the proposed scenarios. The data was collected in Sydney using a survey that contrasted the current road pricing situation with cordon-based and distance-based charging regimes. The model structure considers familiarity and awareness as endogenous variables. The final model identifies statistically significant roles for user charging fees and how revenue raised is to be spent. The endogenous consideration of awareness and familiarity together with risk attitude and perceptual conditioning through beliefs, provide significant information in improving our understanding of how individuals respond through preference revelation to a number of road pricing reforms.